Cooperative Learning: One Step in Answering the Complexity of Islamic Religious Education - Rofi, Sofyan; Setiawan, Bahar Agus; Jatmikowati, Tri Endang; Kusumawati, Dahani; Darmayanti, Husnun Hanifah; Damayanti, Linda (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The complexity of Islamic religious education learning, with its dogmatic and doctrinal patterns, can be a driving factor in students' boredom and passive attitude toward learning activities. This context requires teachers to be able to innovate and be creative in designing active, innovative, creative, and fun learning plans. Steps that can be taken include using cooperative learning models, with various types of existing methods, such as Student Team Achievement Division (STAD) and Two Stay Two Stray (TSTS).Method – This research uses a qualitative approach with a case study type of research. The instrument used in this research is a questionnaire. The data analysis technique uses percentages to determine the level of student perception of the learning model used.Findings – The results of the research prove that, from a student perspective, these two methods, which are part of the cooperative learning model, are very effective in improving student achievement and learning outcomes in Islamic religious education. The effectiveness of the Two Stay Two Stray (TSTS) method from the student perspective reached 83.9 percent. The percentage value for the Student Team Achievement Division (STAD) is 85.5 percent. Research Implications – Using the TSTS and STAD models, which are part of the cooperative learning approach, has very good implications for increasing the effectiveness of Islamic religious education learning in schools. The adaptive nature of these two models can bridge the characteristics of Islamic religious education, which has dogmatic and doctrinal aspects. The results of this research confirm that TSTS and STAD can concretely and effectively improve student learning outcomes in Islamic religious education.